SOME DIFFERENCES IN THE SIZE OF TEETH IN ADOLESCENTS OF DIFFERENT SOMATOTYPES - Smaglyuk, L.V.; Sheshukov, D.V. (World of Medicine and Biology, 2018)
To restore optimal teeth configuration or dentition dental professionals should take into account the morphological parameters of the teeth, their interdependence in the shape of the dentition, the state of occlusion, as well as other constitutional parameters of the human body. Hence, the issues on developing aesthetic criteria in terms of size of teeth considering the constitutional characteristics of the body are remaining relevant. The purpose of this study was to identify the peculiarities of the size of the teeth in adolescents depending on their constitutional and typological parameters of the body structure.The clinical trial included 181 students (85 male and 96 female) aged 21-25 years, whose average age was 23.09 + 0.11 years. Using previously obtained anthropometric findings we evaluated constitutional type of the male and female participants by L.Rees-HJEisenk, 1945. Depending on the value of the index, all the subjects examined, regardless of sex, were divided into three somatotypes: hypersthenic type (index value is less than 96), normosthenic type (index value ranged from 96 to 106) and asthenic type (the index value is over 106). The status of occlusion was assessed according to E. Angle classification (1906). In all the examined individuals, the impressions were taken for making control and diagnostic models. Evaluating the measurements of control and diagnostic models, we paid special attention to mesiodistal dimensions of 12 teeth of the upper and lower jaws.The analysis of the quantitative parameters obtained during the examination of patients was carried out by using mathematical statistics methods with the calculation of the average sample values (M), dispersion (σ) and errors of mean values (m). The calculations were performed on a personal computer using Microsoft Excel 2007, NCSS 2004 and SPSS for Windows. Release 13.0. Normostenic type was found out as the most common type of body structure in 99 (54,69%) male and female individuals studied. The asthenic type was identified in 52 (28.74%) adolescents, and 30 (16.57%) individuals were found out to have the hypersensitivity type of the body structure. The comparative analysis of the size of the maxillary teeth has demonstrated that the canines in the individuals of the hypersthenic type are of a larger mesiodistal size than in the individuals of normosthenic type (p
Keywords: morphological parameters of the teeth; state of occlusion; teeth somatotypes; mesiodistal dimensions; asthenic type; hypertesthenic; normostenic adolescents